Integration and testing of a digital transceiver for a dual frequency, pulse-doppler radar - Du Plessis, Dane (Department of Electrical Engineering, 2017)
This dissertation focuses on the development of a digital transceiver system for a dual-band, polarimetric radar, which is to form part of the NeXtRAD multistatic radar. NeXtRAD is being developed as an instrument for research into the behaviour of clutter and targets as observed by multistatic radars. The Pentek Cobalt model 71621 software defined radio interface was procured for use as the digital transceiver in the system. The goal was to develop the software needed to use this product as the digital transceiver in a prototype version of the NeXtRAD active node, and to ensure that it could be readily integrated with other subsystems in the final system. The active node is essentially a monostatic pulse-doppler radar. Laboratory tests of the transceiver showed that it was possible to generate and digitize pulsed waveforms at a 125 MHz intermediate frequency which is used by the existing receiver exciter in the system. After extensive laboratory testing and development, phase coherent waveform generation and multichannel digitization was achieved. A low transmit power version of the active node was constructed and tested at both operating frequencies. Equipment used in the testing and development of the digital transceiver included laboratory signal generators, spectrum analyzers and oscilloscopes. The digital transceiver was able to function at pulse repetition rates exceeding 2 kHz, with a single transmit channel and three receive channels active. The lowpowered monostatic prototype system was constructed to test the digital transceiver using a receiver exciter subsystem, RF amplifiers and antennas. This prototype radar was used to take measurements of targets at ranges below 300 m and successfully detected reflections from large structures. Cars and pedestrian traffic were detected by their doppler shifts at both L- and X-band frequencies. The detection of moving and stationary targets confirmed the suitability of the digital transceiver for use in the envisioned multistatic radar system.